Monocytes, particularly nonclassical ones, lose their opsonic and nonopsonic phagocytosis capacity during pediatric cerebral malaria - Vianou, Bertin; Royo, Jade; Dechavanne, Sébastien; Bertin, Gwladys I.; Yessoufou, Akadiri; Houze, Sandrine; Faucher, Jean-François; Aubouy, Agnes (Frontiers in Immunology, 2024)
Introduction Innate immunity is crucial to reducing parasite burden and contributing to survival in severe malaria. Monocytes are key actors in the innate response and, like macrophages, are plastic cells whose function and phenotype are regulated by the signals from the microenvironment. In the context of cerebral malaria (CM), monocyte response constitutes an important issue to understand. We previously demonstrated that decreased percentages of nonclassical monocytes were associated with death outcomes in CM children. In the current study, we postulated that monocyte phagocytosis function is impacted by the severity of malaria infection. Methods To study this hypothesis, we compared the opsonic and nonopsonic phagocytosis capacity of circulant monocytes from Beninese children with uncomplicated malaria (UM) and CM. For the CM group, samples were obtained at inclusion (D0) and 3 and 30 days after treatment (D3, D30). The phagocytosis capacity of monocytes and their subsets was characterized by flow cytometry and transcriptional profiling by studying genes known for their functional implication in infected-red blood cell (iRBC) elimination or immune escape. Results Our results confirm our hypothesis and highlight the higher capacity of nonclassical monocytes to phagocyte iRBC. We also confirm that a low number of nonclassical monocytes is associated with CM outcome when compared to UM, suggesting a mobilization of this subpopulation to the cerebral inflammatory site. Finally, our results suggest the implication of the inhibitory receptors LILRB1, LILRB2, and Tim3 in phagocytosis control. Discussion Taken together, these data provide a better understanding of the interplay between monocytes and malaria infection in the pathogenicity of CM.